PEMBENTUKAN KELOMPOK DAN GAYA HIDUP HEDONIS STUDI KASUS : PADA SISWA SMA N 9 PEKANBARU - Dahayu, Rita; Asriwandari, Hesti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The times bring society in the era of modernization full development of the aspects of social life, economy, politics, law, culture, and current technology and education is characteristic of the times. in view of the development of this era then it can definitely say that there is no society that does not change. In conscious or unconscious process of change that is understood by social changes that provide a variety of consequences for society at large. Developments in science and technology (Science and Technology) in view of the context of communication ultimately provide the opportunity for the world community to showcase and demonstrate their culture to others through intenet and television media. Exchange of information and culture in the communications world finally got a good response even be used as a form of lifestyle by people / other cultures. In society modern life, there are interrelationships - behind and can not be separated between the existence of the image and lifestyle . Lifestyle as a differentiator group will appear in society formed on the basis of social stratification. each group in a particular social structure will have a distinctive lifestyle. can be said that this lifestyle was the one who became a symbol of prestige in social stratification social. Starata marked by a different lifestyle.The method used in this paper is a qualitative descriptive. where the data that appears is the word - the word that is usually prepared in the form of expanded text. More dataanalysistechniquesusingcrosscheckinformation.JomKeywords: lifestyle, hedonistic, student behavio